Exchange rate fluctuation and Economic Growth of Laos - SIPHADA, Vatthanaly; PHONGSAVATH , Phetdamone (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
In this paper, we investigate the relationship between exchange rate and economic growth of Laos by using secondary data for the period of 1998-2019. Multi-regression based on VAR model technique has been used for analysis the relation between independent variables and dependent variable. The economic growth is considered as dependent variable, the exchange rate of Lao Kip per Thai Baht, exchange rate of Lao Kip per US dollar, Inflation rate, and Interest rate have been considered as independent variables. The results of this study are presented that exchange rate has negative relate to economic growth, especially is the exchange rate of Lao Kip per US dollar. If the exchange rate of Lao Kip per US dollar increases by 1% it will decrease economic growth by 0.64%. In the short-term exchange rate of Lao kip per Thai Baht has been correlated positive. One percent increase in exchange rate of Lao kip per Thai Baht will be increase the economic growth by 0.69%. Whereas, in the long-term they will be negative effects together. Just as the inflation rate has negative impacted to economic growth, if inflation increase 1% it will be decrease economic growth by 0.01% and interest rates has positive related with the economic growth. We also found that the independent variables dose not Granger cause dependent variable, but dependent variable dose Granger cause to independent variables. The economic growth has high effect to exchange rate of Lao Kip per Thai Baht and per US dollar as 45.83% and 58%, respectively. In addition, the exchange rate of Lao Kip per Thai Baht is significantly to Lao inflation and interest rates higher than exchange rate of Lao Kip per US dollar. Finally, this paper has been some suggestion of exchange rate control policy as a guide for the government.